Analisis Pengaruh Kepemimpinan, Motivasi, Lingkungan Kerja, dan Kedisplinan Terhadap Kinerja Karyawan (Studi Kasus: Operator Welding 1A, PT. XYZ Motor) - Dina Rahmayanti; Idham Afandi (Jurnal Optimasi Sistem Industri, 2014)
Leadership, motivation, work environment, and discipline is some of important factors where its influence in employees performance need to be studied, in order to improve better performance or provide positive influence on the performance itself. Employees performance in the welding section 1 A, has significant effect in the production process at PT. XYZ Motor, which manufactures parts of the body frame, in order to complete the daily production target, the influence of these factors on the employees performance needs to be determined. This study uses a questionnaire for collecting data from samples of 80 respondents taken from 158 employees in the welding 1 A. Multiple linear regression is used to test hypotheses for each variable. Result showed that the discipline variables has positive influence on employee performance with significance value of 0,04, where the value is less than 0,05. Other factors has value greater than 0,05.